2016
DOI: 10.20396/bjos.v15i1.8647121
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features of patients with nonsyndromic cleft lip and/or palate in Western Parana

Abstract: Aim: : To describe the clinical, demographic and environmental features associated with NSCL/P (nonsyndromic cleft lip and/or palate) patients born in western Parana state, Brazil. Methods: This cross-sectional, observational, retrospective study included 188 patients attended at the Association of Carriers of Cleft Lip and Palate - APOFILAB, Cascavel-Parana, between 2012 and 2014. Information on demographic characteristics, medical and dental histories and life style factors were obtained from records and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…[10] Observations carried out on the data from Yayasan Surabaya CLP Center provide results that cleft variation is divided into three types, namely CLP, CL, and CP, which is a type of non-syndromic cleft. This is in accordance with a study conducted by Moreira et al, [11] in 2016, which states that basically the CL/P is divided into CLP, CL, and CP.…”
Section: Discussionsupporting
confidence: 93%
“…[10] Observations carried out on the data from Yayasan Surabaya CLP Center provide results that cleft variation is divided into three types, namely CLP, CL, and CP, which is a type of non-syndromic cleft. This is in accordance with a study conducted by Moreira et al, [11] in 2016, which states that basically the CL/P is divided into CLP, CL, and CP.…”
Section: Discussionsupporting
confidence: 93%
“…The overall breakdown of cleft types found in the present study was what was expected: 71% of the sample had cleft lip with or without palate, and 28% had cleft palate only (8)(9)(10). The distribution by sex was also within the expected proportions (10,11).…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, in some studies were observed differences in the distribution of NSCL/P between males and females 9,10 . Investigating the epidemiological features of NSCL/P patients treated at a reference association in Cascavel-Parana, Brazil, Moreira et al 20 revealed that CLO, CLP and CPO prevailed in males. Studies on Brazilian populations showed a predominance of CLP, followed by isolated CL, and CP 9,21 .…”
Section: Discussionmentioning
confidence: 99%